Impact Investing: Will Hype Stall its Emergence as an Asset Class? - Alto, Philo (Institutional Knowledge at Singapore Management University, 2012)
From when it was first coined five years ago, “impact investing” has now become more mainstream for traditional investors. However, Philo Alto argues that its development is lagging behind the promise of what it can do, and this, in turn, is hampering its emergence as an asset class in its own right.